Chemical Composition and Antibacterial Activity of the Essential Oils of the Amazon Annona Species - Joelma Moreira Alcântara; Juliana Mesquita V. M. de Lucena; Marcia Ortiz Mayo Marques; Jennifer Araújo Oliveira Lima; Maria da Paz Lima (Orbital: The Electronic Journal of Chemistry)
This study evaluated the chemical composition of essential oils (EOs) obtained through hydrodistillation from four Annona species native to the Amazonas state: Annona amazonica R.E. Fr. (commonly known as “envireira”), Annona mucosa Jacq. (“biribá”), Annona exsucca DC. ex Dunal (“araticum”), and Annona insignis R.E. Fr. (“araticum”). Additionally, their antibacterial activities were assessed. Using GC-FID and GC-MS, the major compounds identified were β-caryophyllene, from the leaves of Annona amazonica (14.7%) and A. exsucca (22.2 and 15.3%), γ-muurolene (20.2 and 15.4%) from the leaves of A. exsucca, caryophyllene oxide from the leaves of A. insignis (35.4%), (Z)-nerolidol from the fruits of A. mucosa (38.2%). The EO from A. exsucca, rich in γ-muurolene (20.2%), exhibited significant antibacterial activity against the gram-positive bacterium Streptococcus sanguinis (MIC: 10 μg.mL-1).